Translation shift and the equivalence in childrenâ€™s novel â€œThe House at Pooh Cornerâ€ - Wulansari, Atsani; Arvianti, Gilang Fadhilia; Wulanjani, Arum Nisma; Annafi', Salma (EduLite: Journal of English Education, Literature and Culture, 2023)
Translating literary works such as novels, poetry, short stories, and dramas is widely conducted in Indonesia to introduce literature to the Indonesian people. In translating literary works, the transfer of messages from the source language must be appropriate and flexible in the target language because literary works have their aesthetic function, so translators need to have a broad knowledge of the qualified sociocultural background. Translators do not only translate meaning but also translate the values of literary works such as moral value and cultural value. The role of translators is to find out the equivalence in the target language and use their creativity to solve the non-equivalence in the target text. Equivalence is the main concept to achieve translation quality. This study aims to find the type of translation shift that occurred in the translated version of the children’s book entitled ‘The House at Pooh Corner’ based on Catford theory and to analyse the equivalence of translation according to Popovic. This research is qualitative research which applies content analysis. The data was collected through documentation. It is found that there are level shifts and category shifts in the translated version of The House at Pooh Corner. In addition, the types of equivalence found in this research are paradigmatic equivalence, stylistic equivalence, and textual equivalence. This research is expected to be used as the material for students to understand more about shifts and equivalence in literary translation